2019
DOI: 10.2217/epi-2019-0101
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Profiles and Functional Analysis of Circular RNAS in Children with Fulminant Myocarditis

Abstract: Aim: To assess differential expression profiles of circular RNAs (circRNAs) and explore their possible functions in children with fulminant myocarditis. Materials & methods: circRNA microarray experiments were carried out for determining differential expression profiles of circRNAs in three children with fulminant myocarditis and three healthy volunteers. Functional analysis and circRNA–miRNA–mRNA interaction network building were conducted to study biological functions. Results: This work identified 2281 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…Many researchers have found that circRNAs play an important role in cardiovascular diseases such as myocardial infarction, heart failure, and atherosclerosis (Wang K. et al, 2016 ; Wang et al, 2017 ; Zhang F. et al, 2018 ). Zhang et al confirmed that circRNAs were differentially expressed in fulminant myocarditis, and further bioinformatic analysis showed that many inflammatory or immune pathways, including TNF signaling pathway, Th1 and Th2 cell differentiation and T cell receptor signaling pathway, were involved in VMC (Zhang L. et al, 2019 ). Therefore, circRNAs may be a new therapeutic target for VMC by regulating the immune-inflammatory pathway.…”
Section: The Role Of Circrnas In Vmcmentioning
confidence: 97%
“…Many researchers have found that circRNAs play an important role in cardiovascular diseases such as myocardial infarction, heart failure, and atherosclerosis (Wang K. et al, 2016 ; Wang et al, 2017 ; Zhang F. et al, 2018 ). Zhang et al confirmed that circRNAs were differentially expressed in fulminant myocarditis, and further bioinformatic analysis showed that many inflammatory or immune pathways, including TNF signaling pathway, Th1 and Th2 cell differentiation and T cell receptor signaling pathway, were involved in VMC (Zhang L. et al, 2019 ). Therefore, circRNAs may be a new therapeutic target for VMC by regulating the immune-inflammatory pathway.…”
Section: The Role Of Circrnas In Vmcmentioning
confidence: 97%
“…These targeted pathways are known, critical mediators for the clinical outcomes for SARS-CoV-2-infected patients and give us insight about virus pathophysiology. It is well established that for enveloped viruses, such as SARS-CoV-2, N-or O-glycosylation of S protein determines the viral entry and membrane fusion with functional elicitation of host immune responses [46]. The high-resolution LC-MS/MS experiment was performed to detect site-specific quantitative N-linked and O-linked glycan profiling on SARS-CoV-2 subunit S1 and S2 proteins.…”
Section: Mir-8066mentioning
confidence: 99%
“…In addition, the microarray data revealed that MAPK14 was upregulated in MC. Based on these intriguing findings, we hypothesized that hsa_circ_0071542 might regulate the expression of MAPK14 by binding to hsa-miR-8055 through the interactions of circRNA-miRNA-mRNA network 42 . Hsa_circ_0071542 is derived from the ACSL1 pre-mRNA transcript.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous investigations have provided a comprehensive expression profile of differentially expressed circRNAs, among which the expression of hsa_circ_0071542 was significantly ( p < 0.05) upregulated in children with FM pathology 42 . This result was further validated by microarray analysis and quantitative real-time polymerase chain reaction (qRT-PCR) assay as well.…”
Section: Introductionmentioning
confidence: 99%